BestL1-approximations of classes $W_1^r$ by Splines from $W_1^r$ - Babenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We obtain the exact values of the best $L_1$-approximations of the classes $W_1^r$ of periodic functions by periodic polynomial splines of degree $r$ and defect 1 with equidistant knots that belong to the class $W_1^r$.